Preparation method and application of shape memory organic hydrogel with heterogeneous phase change

The shape memory organic hydrogel prepared by a one-step emulsion thermal polymerization method uses specific components to form shielding performance mainly based on electromagnetic wave absorption, solving the impedance matching and resource waste problems of traditional metal-based materials, and achieving efficient electromagnetic shielding and fast shape memory.

CN119569940AActive Publication Date: 2025-03-07BEIHANG UNIV

Patent Information

Application Number
CN202411332315.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-03-07
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

Traditional metal-based electromagnetic interference shielding materials have contradictions in electromagnetic wave shielding and absorption, and the shape cannot be changed after curing, resulting in waste of resources and poor application flexibility.

Method used

The shape memory organic hydrogel with heterogeneous phase transition was prepared by a one-step emulsion thermal polymerization method, and components such as acrylamide, two-dimensional material MXene, nanoclay, laurel methacrylate and paraffin were used to form shielding properties mainly based on electromagnetic wave absorption.

Benefits of technology

It realizes organic hydrogels with significant tensile, stability and thermomechanical properties under high phase transitions, and has excellent electromagnetic absorption and fast shape memory response capabilities, solving the impedance matching and resource waste problems of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569940A_ABST
    Figure CN119569940A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of shape memory organic hydrogel with heterogeneous phase change, and belongs to the technical field of material scientificity, the organic hydrogel is prepared through a one-step emulsion thermal polymerization method, and the organic hydrogel not only shows remarkable stretchability under the phase change exceeding 1100%, but also has good shape memory performance under the phase change exceeding 1100%. The prepared electromagnetic shielding material has the advantages of excellent mechanical property, excellent stability, excellent thermal mechanical property, excellent recoverability, good shape memory effect, excellent electromagnetic absorption capability and electromagnetic shielding performance with absorption as a main component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material science, and in particular to a preparation method and application of a shape memory organic hydrogel with heterogeneous phase change. Background Art

[0002] With the increasing popularity of micro-electrical equipment, wireless communication equipment and home WIFI transmitters, electromagnetic radiation pollution problems are inevitable, which may cause serious harm to human health, information security and the normal operation of precision equipment.

[0003] Traditional metal-based EMI shielding materials, including iron, nickel, copper and silver, have been developed and explored for their high conductivity for efficient EMI shielding, which is due to the impedance mismatch between free space and shielding materials. Metals exhibit EMI shielding performance dominated by reflection through the accumulation of charge carriers (electrons or holes) at the dielectric interface. However, electromagnetic waves are severely reflected on the surface of these materials (usually more than 90%), causing unbearable secondary electromagnetic radiation pollution, affecting the stability and accuracy of precision electronic devices.

[0004] High magnetic permeability can cause strong natural resonance and eddy current loss between the shielding material and the microwave. Therefore, the material with high magnetic permeability can provide more effective electromagnetic absorption and greatly reduce the secondary electromagnetic radiation. However, due to its low conductivity, it is difficult for such materials to show high electromagnetic shielding interference effectiveness. On the other hand, the conductive network constructed in the electromagnetic shielding material is usually uniform and has constant conductivity. Absorption-type electromagnetic interference shielding materials require good impedance matching so that electromagnetic waves can enter the interior of the material and have strong electromagnetic dissipation capabilities. However, good impedance matching and strong loss capacity are a contradictory combination. Good impedance matching usually means weak loss capacity, while strong loss capacity often means poor impedance matching. In addition, once the traditional shielding material is manufactured, it presents a fixed shape and cannot be re-edited and recycled, resulting in a waste of resources and hindering the flexibility and comprehensiveness of the application.

[0005] Hydrogels have mechanical elasticity, flexibility, fatigue resistance and stretchability. The network structure of hydrogels is rich in water molecules, which can achieve impedance matching without causing unnecessary reflections. However, the conductivity of such hydrogels is usually very low, resulting in a trade-off between impedance matching and conductivity. Summary of the invention

[0006] In view of the above problems, the present invention provides a method for preparing a shape memory organic hydrogel with heterogeneous phase change and its application. The organic hydrogel is prepared by a one-step emulsion thermal polymerization method. The organic hydrogel not only exhibits significant stretchability, excellent stability, thermomechanical properties and recyclability, and good shape memory effect at a phase change of more than 1100%, but also has excellent electromagnetic absorption capacity, showing absorption-based electromagnetic shielding performance.

[0007] One object of the present invention is to provide a shape memory organic hydrogel with heterogeneous phase change, comprising acrylamide, two-dimensional material MXene, nanoclay, lauryl methacrylate and paraffin;

[0008] The electromagnetic wave absorption rate of the organic hydrogel is 80%; the electromagnetic wave absorption temperature is 70° C.; the frequency range of the electromagnetic wave is 12.4 to 18 GHZ;

[0009] The organic hydrogel exhibits good electromagnetic shielding performance in the Ku band and exhibits absorption-dominated electromagnetic shielding properties at 70°C.

[0010] Preferably, the organohydrogel completely recovers to its original shape within 22-25 seconds at 70-80°C.

[0011] Furthermore, the organohydrogel completely recovered to its original shape within 25 seconds at 70°C.

[0012] The organic hydrogel prepared by the present invention has good shape memory function to cope with complex real-life environments, can completely recover to its original shape within 25 seconds at 70° C., and has rapid shape memory response capability.

[0013] Another object of the present invention is to provide a method for preparing a shape memory organohydrogel with heterogeneous phase transition, comprising:

[0014] Step 1, mixing two-dimensional material Mxene, acrylamide and nanoclay, and adding surfactant and crosslinking agent 1 to obtain an aqueous solution;

[0015] Preferably, the specific steps of obtaining the aqueous phase solution in step 1 include:

[0016] Add acrylamide (AAm) and nanoclay to the two-dimensional material MXene nano-water solution, stir, and continue to add surfactant and cross-linking agent 1 to obtain an aqueous phase solution;

[0017] Step 2, after melting the paraffin, adding lauryl methacrylate and a second crosslinking agent to obtain an oil phase solution;

[0018] Step 3, adding the aqueous phase solution to the oil phase solution, shearing evenly, to obtain an oil-in-water emulsion;

[0019] Step 4: Add ammonium persulfate and an initiator to the oil-in-water emulsion, stir, and perform curing and cross-linking to obtain a shape memory organic hydrogel with heterogeneous phase change.

[0020] Preferably, the two-dimensional material MXene in step 1 is a metal carbide and metal nitride material with a two-dimensional layered structure;

[0021] The volume of the two-dimensional material MXene aqueous solution is 10-30 ml;

[0022] Preferably, the mass ratio of the acrylamide to the nanoclay in step 1 is 3-9:0.8-2.4;

[0023] Furthermore, the mass of the acrylamide is 3 to 9 g; the mass of the nanoclay is 0.8 to 2.4 g;

[0024] Furthermore, the nanoclay may be montmorillonite or halloysite;

[0025] Preferably, the stirring speed in step 1 is 500-800 rpm, the stirring time is 10-15 min, and the stirring temperature is 50-55° C.;

[0026] Preferably, the surfactant in step 1 is sodium dodecyl sulfate (SDS);

[0027] Preferably, the cross-linking agent in step 1 is N,N'-methylenebisacrylamide (MBA);

[0028] Preferably, the melting temperature in step 2 is 50-55°C;

[0029] Preferably, the second cross-linking agent in step 2 is ethylene glycol dimethacrylate;

[0030] Preferably, the mass ratio of the paraffin wax, lauryl methacrylate and the second crosslinking agent in step 2 is 7.5-10.5:4.5-9:0.13;

[0031] Preferably, the molar mass ratio of the cross-linking agent 1 to the cross-linking agent 2 is: 20:13;

[0032] Further, the mass of the paraffin wax is 7.5-10.5 g; the mass of the lauryl methacrylate LMA is 4.5-9 g;

[0033] Preferably, the mass ratio of ammonium persulfate (APS) to initiator is: 3:10;

[0034] Further, the mass of the ammonium persulfate (APS) is 15-20 mg;

[0035] The initiator is 2,2-azobisisobutyronitrile (AIBN) (EGDMA);

[0036] Preferably, the stirring speed in step 2 is 500-800 rpm;

[0037] Preferably, the uniform shearing in step 3 is performed by using a high-speed shear homogenizer under the action of a high-speed shear force;

[0038] The rotation speed of the high-speed shearing homogenizer is 10000-10500 rpm, and the shearing time is 10-20 minutes.

[0039] Preferably, the stirring speed in step 4 is 400-500 rpm, and the stirring time is 2-3 minutes;

[0040] In the present invention, high-speed stirring is required in step 3 to uniformly stir the water-oil phase, and in step 4, only the ammonium persulfate needs to be uniformly distributed.

[0041] Preferably, the curing and cross-linking temperature in step 4 is 70-80° C., and the curing and cross-linking time is 2.5-3 h; and the curing and cross-linking container is a vacuum oven.

[0042] The present invention simplifies the difficulty of synthesizing MXene / CNF / AAm organic hydrogel by a one-step thermal polymerization method. The technical solution of the present invention adds nanoclay, which plays an important role. On the one hand, it acts as a Pickering emulsifier, adsorbed on the oil-water interface to prevent oil droplets from agglomerating. On the other hand, it acts as a multifunctional crosslinker in the water phase, effectively inhibiting the aggregation of oil droplets and keeping the emulsion morphology stable. The continuous water phase network wraps and separates individual paraffin droplets, thereby evenly distributing the domains of paraffin microspheres throughout the material. Therefore, these microsphere domains can serve as micro-inclusions of the organic gel, providing good shape memory properties and excellent thermomechanical properties.

[0043] Another object of the present invention is to provide a shape memory organic hydrogel with heterogeneous phase change for use in the field of electromagnetic shielding.

[0044] In the technical solution of the present invention, when electromagnetic waves are incident on the hydrogel, the non-conductive paraffin adjusts the appropriate conductivity to cause impedance matching, and most of the electromagnetic waves enter the interior of the organic hydrogel material; the presence of the two-dimensional material Mxene and nanoclay forms a conductive network, and the conduction loss of the two-dimensional material Mxene and nanoclay promotes the absorption of electromagnetic waves. In addition, the charge carriers will generate microcurrents, resulting in ohmic losses and energy dissipation of electromagnetic waves. At the same time, the honeycomb network structure composed of the paraffin shell, the two-dimensional material Mxene and the nanoclay water phase reflects and scatters the electromagnetic waves multiple times; there are a large number of polar water molecules in the organic hydrogel material, which have dipole moments and form dipole polarization under the action of electromagnetic waves, further attenuating the electromagnetic wave energy; on the other hand, a large number of free charges are accumulated at the heterogeneous interface between the aqueous solution and the oil solution. These free charges can act as scattering sites, resulting in interfacial polarization loss; when the temperature rises, the paraffin changes from solid to liquid, and becomes ellipsoidal under the action of tensile stress, with an increase in specific surface area. Electromagnetic waves will form scattering domains inside, increasing the wave propagation path and promoting greater dissipation of electromagnetic wave energy.

[0045] The MXene / CNF / AAm organic hydrogel prepared by the present invention not only has excellent tensile properties, excellent thermomechanical properties and shape memory effect, but also has good environmental stability and can be applied on a large scale. At the same time, the heterogeneous phase change organic hydrogel prepared by the invention exhibits a high strain capacity with rapid recovery during the shape memory process. Due to the moderate conductivity of the two-dimensional material MXene network and the stable water-oil phase heterogeneous interface state and the rich internal water environment, the organic hydrogel exhibits electromagnetic shielding behavior dominated by absorption. In addition, due to the phase change effect of liquid paraffin, the organic hydrogel with the optimal water-oil ratio has excellent shape memory function and good repeatable stability.

[0046] The MXene / CNF / AAm organic hydrogel prepared by the present invention exhibits high-efficiency electromagnetic interference shielding performance mainly based on absorption by optimizing the ratio of water phase to oil phase in the organic hydrogel. The electromagnetic shielding performance can be controlled at different temperatures. A simple and stable two-phase organic hydrogel is demonstrated, and its comprehensive performance is better than that of most existing electromagnetic shielding hydrogel composite materials, and provides a reference for exploring more excellent electromagnetic shielding composite materials.

[0047] Compared with the prior art, the present invention has at least the following beneficial effects:

[0048] (1) The organic hydrogel of the present invention optimizes its mechanical properties by precisely controlling the ratio of water to oil phases; it has excellent electromagnetic shielding effectiveness mainly based on absorption and controllable electromagnetic shielding performance;

[0049] (2) The method for preparing the organic hydrogel prepared by the present invention is efficient and stable, the process is simple and feasible, and the conditions for synthesizing the organic hydrogel are thermal polymerization at 70° C., which reduces the difficulty of material synthesis and improves the synthesis efficiency of the material;

[0050] (3) The organohydrogel prepared by the present invention not only has excellent tensile properties, excellent thermomechanical properties and shape memory effect, but also has good environmental stability and can be applied on a large scale;

[0051] (4) The heterogeneous phase-change organic hydrogel prepared by the present invention exhibits high strain capacity with rapid recovery during the shape memory process. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] The drawings are only for the purpose of illustrating particular embodiments and are not to be construed as limiting the invention.

[0053] Figure 1 Schematic diagram of the preparation process of MXene / CNF / AAm organohydrogel prepared in Example 1 of the present invention;

[0054] Figure 2 Schematic diagram of the physical pictures of different water-oil ratios of MXene / CNF / AAm organohydrogels prepared in Examples 1-4 of the present invention;

[0055] Figure 3 (a) is a schematic diagram of a scanning confocal microscope (CLSM) of the MXene / CNF / AAm organohydrogel prepared in Examples 1-4 of the present invention; (b) is a schematic diagram of a scanning confocal microscope (CLSM) of the MXene / CNF / AAm organohydrogel prepared in Examples 1-4 of the present invention;

[0056] Figure 4 (a) Schematic diagram of the scanning electron microscope (SEM) image of the MXene / CNF / AAm organohydrogel prepared in Examples 1-4 of the present invention; (b) Schematic diagram of the elemental mapping (EDS) image of the MXene / CNF / AAm organohydrogel prepared in Examples 1-4 of the present invention;

[0057] Figure 5 (a) is a schematic diagram of the stress-strain curves of the MXene / CNF / AAm organohydrogels prepared in Examples 1-4 of the present invention at different water-oil ratios at 25°C; (b) is a schematic diagram of the stress-strain curves of the MXene / CNF / AAm organohydrogels prepared in Examples 1-4 of the present invention at different water-oil ratios at 70°C;

[0058] Figure 6(a) is a schematic diagram of the 200%-1000% stretching cycle curves of the organohydrogel prepared in Examples 1-4 of the present invention at different temperatures (70°C, 25°C); (b) is a schematic diagram of the stretching cycle curves of the organohydrogel prepared in Examples 1-4 of the present invention at different stretching times;

[0059] Figure 7 Schematic diagram of the shape recovery diagram of the MXene / CNF / AAm organohydrogel prepared in Examples 1-4 of the present invention at 70°C;

[0060] Figure 8 (a) is a schematic diagram of the electromagnetic shielding efficiency data graph of the MXene / CNF / AAm organohydrogel used in Examples 1-4 of the present invention at different water-to-oil ratios; (b) is a schematic diagram of the power coefficient data graph of the MXene / CNF / AAm organohydrogel used in Examples 1-4 of the present invention at different water-to-oil ratios;

[0061] Fig. 9 Schematic diagram of the change in the average standard error of the MXene / CNF / AAm organohydrogel prepared in Examples 1-4 of the present invention during storage at different temperatures. DETAILED DESCRIPTION

[0062] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. In addition, the present invention can also be implemented in other ways different from those described herein, and therefore, the protection scope of the present invention is not limited by the specific embodiments disclosed below.

[0063] A specific embodiment of the present invention, as Figure 1-9 , discloses a preparation method and application of a shape memory organic hydrogel with heterogeneous phase change.

[0064] In order to illustrate the effectiveness of the method proposed in the present invention, the above technical solution of the present invention is described in detail below through a specific embodiment, and the specific implementation steps are as follows:

[0065] An object of the present invention is to provide a shape memory organic hydrogel with heterogeneous phase change, comprising acrylamide, two-dimensional material MXene, nanoclay, lauryl methacrylate and paraffin in a component content ratio of 3-9:0.1-0.3:0.8-2.4:4.5-9:7.5-10.5; the electromagnetic wave absorptivity of the organic hydrogel is 80%; the electromagnetic wave absorption temperature is 70°C; the frequency range of the electromagnetic wave is 12.4-18GHZ;

[0066] The organic hydrogel exhibits good electromagnetic shielding performance in the Ku band and exhibits absorption-dominated electromagnetic shielding properties at 70°C.

[0067] Preferably, the organohydrogel completely recovers to its original shape within 25 seconds at 70°C.

[0068] The organic hydrogel prepared by the present invention has good shape memory function to cope with complex real-life environments, can completely recover to its original shape within 25 seconds at 70° C., and has rapid shape memory response capability.

[0069] Another object of the present invention is to provide a method for preparing a shape memory organohydrogel with heterogeneous phase transition, comprising:

[0070] Step 1, mixing two-dimensional material Mxene, acrylamide and nanoclay, and adding surfactant and crosslinking agent 1 to obtain an aqueous solution;

[0071] Preferably, the specific steps of obtaining the aqueous phase solution in step 1 include:

[0072] Add acrylamide (AAm) and nanoclay to the aqueous solution of two-dimensional material MXene, stir, and continue to add surfactant and cross-linking agent 1 to obtain an aqueous phase solution;

[0073] Step 2, after melting the paraffin, adding lauryl methacrylate and a second crosslinking agent to obtain an oil phase solution;

[0074] Step 3, adding the aqueous phase solution to the oil phase solution, shearing evenly, to obtain an oil-in-water emulsion;

[0075] Step 4: Add ammonium persulfate and an initiator to the oil-in-water emulsion, stir, and perform curing and cross-linking to obtain a shape memory organic hydrogel with heterogeneous phase change.

[0076] Preferably, the two-dimensional material MXene in step 1 is a metal carbide and metal nitride material with a two-dimensional layered structure;

[0077] The volume of the two-dimensional material MXene aqueous solution is 10-30 ml, with 10 mg per ml;

[0078] Preferably, the mass ratio of the acrylamide to the nanoclay in step 1 is 3-9:0.8-2.4;

[0079] Furthermore, the mass of the acrylamide is 3-9 g; the mass of the nanoclay is 0.8-2.4 g;

[0080] Furthermore, the nanoclay may be montmorillonite or halloysite;

[0081] Preferably, the stirring speed in step 1 is 500-800 rpm, the stirring time is 10-15 min, and the stirring temperature is 50-55° C.;

[0082] Preferably, the surfactant in step 1 is sodium dodecyl sulfate (SDS);

[0083] Preferably, the cross-linking agent in step 1 is N,N'-methylenebisacrylamide (MBA);

[0084] Preferably, the melting temperature in step 2 is 50-55°C;

[0085] Preferably, the second cross-linking agent in step 2 is ethylene glycol dimethacrylate;

[0086] Preferably, the mass ratio of the paraffin wax, lauryl methacrylate and the second crosslinking agent in step 2 is 7.5-10.5:4.5-9:0.13;

[0087] Preferably, the molar mass ratio of the cross-linking agent 1 to the cross-linking agent 2 is: 20:13;

[0088] Further, the mass of the paraffin wax is 7.5-10.5 g; the mass of the lauryl methacrylate LMA is 4.5-9 g;

[0089] Preferably, the mass ratio of ammonium persulfate (APS) to initiator is: 3:10;

[0090] Further, the mass of the ammonium persulfate (APS) is 15-20 mg;

[0091] The initiator is 2,2-azobisisobutyronitrile (AIBN) (EGDMA);

[0092] Preferably, the stirring speed in step 2 is 500-800 rpm;

[0093] Preferably, the uniform shearing in step 3 is performed by using a high-speed shear homogenizer under the action of a high-speed shear force;

[0094] The rotation speed of the high-speed shearing homogenizer is 10000-10500 rpm, and the shearing time is 10-20 minutes.

[0095] Preferably, the stirring speed in step 4 is 400-500 rpm, and the stirring time is 2-3 minutes;

[0096] In the present invention, high-speed stirring is required in step 3 to uniformly stir the water-oil phase, and in step 4, only the ammonium persulfate needs to be uniformly distributed.

[0097] Preferably, the curing and cross-linking temperature in step 4 is 70-80° C., and the curing and cross-linking time is 2.5-3 h; and the curing and cross-linking container is a vacuum oven.

[0098] Embodiment 1

[0099] Step 1: Take 15 ml of 2D material MXene aqueous solution (10 mg mL -1 ) was placed in a beaker with a capacity of 40 mL, and then 4.5 g of acrylamide and 12 g of nanoclay were added, and stirred at a magnetic stirring speed of 500 rpm to form a uniform aqueous phase, and then 200 mg of N, N'-methylenebisacrylamide as a cross-linking agent and 1 ml of sodium dodecyl sulfate as a surfactant were added thereto to obtain an aqueous phase solution;

[0100] Step 2, taking 10.5 g of paraffin wax and placing it in a beaker with a capacity of 50 ml, heating it to 55° C., after the paraffin wax is completely melted into liquid, adding 4.5 g of lauryl methacrylate and 0.13 g of ethylene glycol dimethacrylate as a lipophilic crosslinking agent to the molten paraffin wax, stirring at a magnetic stirring speed of 800 rpm for 10 minutes to obtain an oil phase solution;

[0101] Step 3. Mix the prepared aqueous solution and oil phase solution, and shear them at 55°C and 10000 for 5 minutes using a high-speed shear homogenizer. After the mixed liquid is sheared evenly, add 0.03g of ammonium persulfate and 0.1g of 2,2-azobisisobutyronitrile as thermal initiators to the mixed solution, stir at 600rpm for 3 minutes, and then pour into a polytetrafluoroethylene mold, place in a vacuum oven at 70°C for cross-linking polymerization for 2.5h, and the MXene / CNF / AAm organic hydrogel is prepared and placed in a vacuum glove box as sample 1 for subsequent testing.

[0102] Embodiment 2

[0103] The content of the two-dimensional material MXene aqueous solution in step 1 of Example 1 was changed to 20 ml, and the content of paraffin in step 2 was changed to 7 g, while the rest remained unchanged to obtain sample 2 V H :V O =2:1.

[0104] Embodiment 3

[0105] The content of the two-dimensional material MXene aqueous solution in step 1 of Example 1 was changed to 12 ml, and the content of paraffin in step 2 was changed to 12.6 g, and the rest remained unchanged to obtain sample 2 V. H :V O =2:3.

[0106] Embodiment 4

[0107] The content of the two-dimensional material MXene aqueous solution in step 1 of Example 1 was changed to 10 ml, and the content of paraffin in step 2 was changed to 14 g, and the rest remained unchanged to obtain sample 3 V. H :V O =2:4.

[0108] like Figure 2 As shown, the actual photos of samples 1, 2, 3 and 4 prepared in Examples 1 to 4 at different water-oil ratios show that their surfaces are smooth and flat, and they are all round hydrogel sheets with a diameter of 40.0 mm and a thickness of 1.5 mm.

[0109] like Figure 3-4 As shown, the morphology of samples 1, 2, 3 and 4 prepared in Examples 1-4 under scanning confocal microscope and scanning electron microscope can clearly observe the microstructure inside the hydrogel, and the organic hydrogel forms a continuous network. The scanning electron microscope image shows that the oil phase paraffin is tightly encapsulated in the continuous hydrogel network, and the average particle size of the obtained paraffin microspheres is about 20.63um; in the corresponding energy dispersion X-ray spectrum, it can be observed that the two-dimensional material MXene is evenly distributed on the hydrogel network structure.

[0110] like Figure 5-6 As shown, the tensile properties of samples 1, 2, 3 and 4 prepared in Examples 1 to 4 at different ambient temperatures indicate that they have good tensile capacity at different ambient temperatures, ensuring their durability and stability.

[0111] like Figure 7 As shown, samples 1, 2, 3 and 4 prepared in Examples 1-4 have shape programming and shape memory functions at 70°C, indicating their excellent shape recovery ability and good recyclability, ensuring the practicality of the composite organic hydrogel.

[0112] Embodiment 5

[0113] The samples 1, 2, 3 and 4 prepared in Examples 1 to 4 were applied to Ku-band electromagnetic shielding performance testing.

[0114] A vector network analyzer was used to evaluate the electromagnetic shielding performance of samples 1, 2, 3 and 4 prepared in Examples 1-4. The sample size was 5*5 cm square sample with a thickness of 1 mm. The electromagnetic wave frequency range used in the test was 12.4-18 GHz.

[0115] like Figure 8 As shown, the electromagnetic shielding efficiency (SE) of samples 1, 2, 3 and 4 prepared in Examples 1 to 4 under different water-to-oil ratios is shown. T ) and power coefficient; From the data in the figure, we can see that V H :V O=2:1, V H :V O =2:2, V H :V O =2:3 and V H :V O = SE of 2:4 T The values ​​are 48.84, 58.06, 46.61 and 40.02 dB, respectively, which are better than the 20 dB target value of commercial electromagnetic shielding materials. In addition, the absorptivity at 70 ° C is higher than the reflectivity. H :V O =2:2 reaches the optimal value, indicating that the organic hydrogel of the present invention is an electromagnetic shielding material mainly based on absorption.

[0116] Embodiment 6

[0117] The samples 1, 2, 3 and 4 prepared in Examples 1 to 4 were applied to the electromagnetic shielding performance stability test.

[0118] like Figure 7 As shown in the figure, the electromagnetic shielding performance of samples 1, 2, 3 and 4 prepared in Examples 1 to 4 after being stored at 25°C and 70°C for different days. From the data graph, it can be seen that at 70°C, the average SE after 7 days is T The value is stable at 40.38 dB, which can still meet the requirements of commercial applications, indicating that samples 1, 2, 3 and 4 prepared in Examples 1 to 4 have good environmental stability.

[0119] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a shape memory organohydrogel with heterogeneous phase transition, characterized in that: include: Step 1, mixing two-dimensional material MXene, acrylamide and nanoclay, and adding surfactant and crosslinking agent 1 to obtain an aqueous solution; Step 2, after melting the paraffin, adding lauryl methacrylate and a second crosslinking agent to obtain an oil phase solution; Step 3, adding the aqueous phase solution to the oil phase solution, shearing evenly, to obtain an oil-in-water emulsion; Step 4: Add ammonium persulfate and an initiator to the oil-in-water emulsion, stir, and perform curing and cross-linking to obtain a shape memory organic hydrogel with heterogeneous phase change.

2. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 1, characterized in that: The mass ratio of the acrylamide to the nanoclay in step 1 is 3-9:0.8-2.

4.

3. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 1, characterized in that: The mass ratio of the paraffin wax, lauryl methacrylate and crosslinking agent 2 in step 2 is 7.5-10.5:4.5-9:0.

13.

4. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 1, characterized in that: The mass ratio of the cross-linking agent 1 to the cross-linking agent 2 is 20:

13.

5. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 1, characterized in that: The mass ratio of the ammonium persulfate to the initiator is 3:

10.

6. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 1, characterized in that: The uniform shearing in step 3 is performed by using a high-speed shear homogenizer under the action of a high-speed shear force.

7. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 6, characterized in that: The rotation speed of the high-speed shearing homogenizer is 10000-10500 rpm, and the shearing time is 10-20 minutes.

8. The method for preparing the shape memory organohydrogel with heterogeneous phase transition according to claim 1, characterized in that: The curing and cross-linking temperature in step 4 is 70-80° C., and the curing and cross-linking time is 2.5-3 hours.

9. A shape memory organic hydrogel with heterogeneous phase transition, prepared according to the preparation method according to any one of claims 1 to 8, characterized in that: The shape memory organic hydrogel with heterogeneous phase change includes acrylamide, two-dimensional material MXene, nanoclay, lauryl methacrylate and paraffin.

10. An application of a shape memory organic hydrogel with heterogeneous phase transition, characterized in that: The shape memory organic hydrogel described in claim 9 is used for electromagnetic shielding.

Citation Information

Patent Citations

  • Electromagnetic shielding material with self-repairing function and preparation method and application thereof

    CN113773597A

  • Composite hydrogel, preparation method, electromagnetic shielding device and displacement sensor

    CN115260692A

  • Self-adhesive MXene-based electromagnetic shielding hydrogel as well as preparation method and application thereof

    CN117624478A

  • Graphene-containing composite material, preparation method and use thereof

    US20180291157A1

Cited By

  • A high-toughness glassy shape memory hydrogel with polymerization-induced microphase separation and a preparation method and application thereof

    CN122749801A